How does the media report the problems of Bulgarian language instruction in universities - Koeva, Silvia; Topalova, Elitsa (Media and Language, 2022)
The article follows the media coverage of Bulgarian language education in universities. The role media play in forming public opinion is highlighted. The text explores if the Bulgarian language education in universities is covered by the Bulgarian media, whether the issues concerning it are considered relevant and to what extent to journalists impact the perceptions of their audience. Based on a review of popular and niche Bulgarian online media, the study outlines a list of the leading topics, related to the Bulgarian language education in universities.